5 Ellipsoids

5 Ellipsoids

5 Ellipsoids Ellipsoid: Recall that an ellipsoid is a set of the form n > P = fx 2 R :(x − a) A(x − a) ≤ 1g (1) where A is a (positive) definite matrix and a 2 Rn. Here the point a is called the center of n the ellipsoid. Note that the unit ball Bn = fx 2 R : jjxjj ≤ 1g is an ellipsoid. Proposition 5.1 n (i) A set P ⊆ R is an ellipsoid if and only if P is the image of Bn under an affine transformation. − 1 (ii) If P is an ellipsoid given by A; a as in (1), then Vol(P ) = (det(A)) 2 Proof: Let P be given by A; a as in (1). Since A is positive definite, we may write A = U >U where U is invertible. Now, consider applying the affine transformation x ! U(x − a). This maps P to the set > > > U(P ) = fU(x − a):(x − a) U U(x − a) ≤ 1g = fy : y y ≤ 1g = Bn (here Bn is the n-dimensional ball of radius 1). So, this mapping sends P to Bn. The proof of (i) follows immediately from this. For (ii), note that the volume of P is −1 − 1 Vol(P ) = det(U )Vol(Bn) = (det(A)) 2 Vol(Bn): Theorem 5.2 (L¨owner-John) If K ⊆ Rn is compact, then there is a unique ellipsoid LJ(K) of minimum volume containing K. Furthermore, if K is convex, then scaling LJ(K) 1 by a factor of n results in an ellipsoid which is contained in K. Lemma 5.3 Let P ⊆ Rn be an ellipsoid centered at a and let H be a halfspace defined by a hyperplane which contains a. Then there is an ellipsoid P 0 with the following properties: (i) P \ H ⊆ P 0 − 1 (ii) Vol(P 0) ≤ e 2(n+1) Vol(P ) 2 Proof: First consider the special case that P = Bn. In this case, we may assume (by possibly n performing a rotation) that H = fx 2 R : x1 ≥ 0g. We claim that ( 2 n ) (n + 1)2 1 n2 − 1 X P 0 = x 2 n : x − + x2 ≤ 1 R n2 1 n + 1 n2 i i=2 0 1 has the desired properties. First, note that P is an ellipsoid with center ( n+1 ; 0;:::; 0) and (n+1)2 n2−1 matrix A a diagonal matrix with n2 in the first position and n2 in the others. To prove (ii) we need to compute Vol(P 0). Let U be the diagonal matrix with U 2 = A. Then we have 0 Vol(P ) − 1 = (det(A)) 2 Vol(Bn) n−1 n n 2 = n + 1 n2 − 1 n−1 − 1 − 1 1 − 1 ≤ e n+1 e (n2−1)2 = e n+1 e 2(n+1) = e 2(n+1) Here we have used the fact that 1 + x ≤ ex for al x. Now, to prove (i), let x 2 H \ P and observe that 2 n (n + 1)2 1 n2 − 1 X x − + x2 n2 1 n + 1 n2 i i=2 n 2(n + 1) 2(n + 1) 1 n2 − 1 X = x2 − x + + x2 n2 1 n2 1 n2 n2 i i=1 2(n + 1) 1 n2 − 1 ≤ x (x − 1) + + n2 1 1 n2 n2 ≤1: This completes the proof in the special case when P = Bn. For the general case, choose an affine linear transformation f(x) = Bx + b so that f maps P to Bn. Then apply the special case to choose P 0 and then apply the transformation f −1. Since affine transformations preserve volume ratios, this yields a suitable ellipsoid for P . .

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    2 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us